Agricultural growth and investment options for poverty reduction in Rwanda - Diao, Xinshen; Fan, Shenggen; Kanyarukiga, Sam; Yu, Bingxin (International Food Policy Research Institute, 2010)
Agricultural development strategies that are put forward by individual African countries delineate priorities for actions to enhance agricultural and overall development. Understanding alternative agricultural growth options and their linkages with poverty reduction and prioritizing agricultural investments are the two key components of an agricultural development strategy. However, the relationships between growth and poverty reduction and between targeted growth and required public investment arenot straightforward, and solid research is needed to support an evidence-based policymaking process. This monograph provides such a study using Rwanda as a case. An economywide model is developed for the study and is appliedto the most recent economic data and public investment information to analyze agricultural growth and investment options for poverty reduction in Rwanda. The monograph shows that the country's targeted agricultural sub-sector growth, if achieved, would allow Rwanda to meet the ComprehensiveAfrica Agriculture Development Programme (CAADP) target of 6 percent annual growth in agricultural gross domestic product (GDP) by 2020. With comparable growth in the nonagricultural sector, rapid economic growth would result in the national poverty rate falling to 35.5 percent by 2015, a reduction of 25 percentage points over the 1999 rate. Although the majority of rural households benefit from rapid agricultural growth, the most vulnerablehouseholds—those with very small landholdings and with few opportunities toparticipate in the production of export crops—appear to benefit less. The reportshows that economywide growth led by the agricultural sector has a greatereffect on poverty reduction than does the same level of growth driven bythe nonagricultural sector. Among agricultural subsectors, growth driven mainlyby increased productivity in staple crops has the greatest poverty reduction effect.